STRATEGI PEMANFAATAN TEMPAT EVAKUASI SEMENTARA KECAMATAN PEUKAN BADA KABUPATEN ACEH BESAR - Amalia Herman; Teuku Budi Aulia; Ashfa Achmad (Prodi Magister Teknik Sipil Unsyiah, 2018)
The disaster phenomenon has encouraged regions to rearrange community life including in Aceh Besar district which is an area affected by earthquake and tsunami. Nowadays the government concern to handling a natural disaster by constructing the Temporary Evacuation Shelter (TES). Therefore, this study aiming at gaining society perception of TES, and determining the main factor and the strategies on the use of TES. The benefits are to provide information and input to the Government and the management of TES. Quantitative and qualitative methods were used in this study. The questionnaire was distributed to the target respondents as much as 233 questionnaires. Furthermore, Focused Group Discussion (FGD) held by invited society figure and stakeholders to obtain the strategies of the use of TES. Results from the analysis questionnaire data indicate that people secured with the existence of TES. The main factor is the availability of TES facilities. The conclusion from FGD is introducing TES early by including disaster curriculum in school, developing local wisdom from good habits that is preparing a family mitigation planning. Moreover, the BPBD Aceh Besar should be aware of the availability of facilities of TES and prepare a disaster mitigation plan on community base considering the children, elderly and disabilities.